Estudio geológico – geotécnico para el emplazamiento del relleno sanitario en la parroquia 27 de Abril, cantón Espíndola, provincia de Loja. - Saavedra Jiménez, Darlinton Joel (2024)
Geological and geotechnical studies were carried out in order to understand the physical and mechanical characteristics of the materials that make up the study area, with the objective of assess the feasibility of locating a sanitary landfill in the parish of 27 de Abril, in the canton of Espindola, province of Loja. This was due to the fact that the current landfill is in the process of closure. The studies were executed at the beginning of the year 2023 and interpreted in the same period. This research project was carried out in a 4-hectare area, proposed by the Decentralized Autonomous Government (GAD) of Espíndola as an option for the construction of this civil work. A series of tasks were developed, including topographic survey, geological study, geotechnical study, slope analysis, and zoning based on soil bearing capacity and permeability. From a geological perspective, the area is mainly composed of fine soils with loamy and clayey characteristics, as well as tuffs with a sandy matrix, typical of the Sacapalca formation, covering more than 80% of the 27 de Abril parish. To obtain this information, outcrop surveys were conducted both inside and outside the study area, in addition to the excavation of test pits for even greater precision. Geotechnical characterization was carried out based on S.P.T and permeability tests, complemented by geological survey and laboratory tests on samples obtained from the exploration, allowing the determination of the underlying soil stratigraphy and its mechanical properties. Based on the information collected throughout the research, a geotechnical zoning was carried out. Areas with specific characteristics were identified, and the location that exhibited the best conditions for the placement of the Espíndola canton's Sanitary Landfill was selected. Keywords: Landfill, Zoning, Bearing Capacity, Permeability.